Geomechanical Behavior of Bio-Cemented Sand for Foundation Works - Youventharan, Duraisamy (IntechOpen, 2019)
Bio-cementation is an innovative green technology that complements existing ground improvement techniques, but it is yet to be proven for large-scale foundation works. Previously attention has been focused on strategies to inject the bacteria and nutrients to produce the cement in the ground. This study looks at the performance of geomechanical response when the bacteria and nutrients are mixed in sand, an approach that is used in producing cemented soil columns. To explore the mechanical response of bio-cemented soil, results from unconfined compressive strength (UCS) tests and triaxial tests have been analyzed to understand the effects of bio-cementation for sand in contrast to alternative cement, gypsum. The stiffness has also been monitored using bender element techniques in triaxial cell. Both the shear wave signals during the cementation phase and the shearing phase were recorded using this technique. The results show that for a given amount of cement, higher resistances are measured for the bio-cemented samples compared to gypsum. The mixing process is shown to produce homogeneous bio-cemented samples with higher strength and stiffness than the technique of flushing or injection commonly used, provided the amount of calcite is less than 4%. The results show that the bio-cement produces similar mechanical behavior to other artificially cemented sands.